2021
DOI: 10.1038/s41398-021-01315-9
|View full text |Cite|
|
Sign up to set email alerts
|

Attentive brain states in infants with and without later autism

Abstract: Early difficulties in engaging attentive brain states in social settings could affect learning and have cascading effects on social development. We investigated this possibility using multichannel electroencephalography during a face/non-face paradigm in 8-month-old infants with (FH, n = 91) and without (noFH, n = 40) a family history of autism spectrum disorder (ASD). An event-related potential component reflecting attention engagement, the Nc, was compared between FH infants who received a diagnosis of ASD a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 92 publications
0
12
0
Order By: Relevance
“…The current finding also suggests that attention allocation and visual processing and how these processes are supported by sensorimotor processes, such as eye movement control, during the resting‐state task may differ between groups. A recent study showed that microstates occurring during gaze to a face is predictive of autism spectrum diagnosis in infants (Gui et al., 2021). Thus, our future work will include examinations of changes in microstates in a specific task context, such as visual exploration and attention control.…”
Section: Discussionmentioning
confidence: 99%
“…The current finding also suggests that attention allocation and visual processing and how these processes are supported by sensorimotor processes, such as eye movement control, during the resting‐state task may differ between groups. A recent study showed that microstates occurring during gaze to a face is predictive of autism spectrum diagnosis in infants (Gui et al., 2021). Thus, our future work will include examinations of changes in microstates in a specific task context, such as visual exploration and attention control.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, only a few other studies using a microstate approach in individuals with ASD have been published (49)(50)(51)(52)(53)(54)(55). Across resting-state studies, D'Croz-Baron and colleagues found six microstate maps that best described their dataset during an eyes-closed condition (49).…”
Section: Discussionmentioning
confidence: 99%
“…At the start of each block, one of the face stimuli was selected to be sampled. This stimulus was repeatedly presented for a total of 12 trials per block; we decided to present 12 trials in each block as this number of trials was 20% higher than the typical minimum trial number (10) used in infant Nc studies to allow for data loss (Munsters et al 2019, Gui et al 2021. Each block started with a red spiral to attract the infants' attention to the screen.…”
Section: Methodsmentioning
confidence: 99%
“…The success of BO-based approaches are dependent on reliable and meaningful neural signatures to be used as target metrics. In the current proof-of-concept study, we chose our parameters and measures for the ERP features based on the previous literature and offline analysis of pilot and existing datasets (Gui et al 2021). The preprocessing methods and calculation of ERP features however vary between studies.…”
Section: Methodological Considerationsmentioning
confidence: 99%
See 1 more Smart Citation